Elementos da cinematografia: um estudo à análise fílmica de “Footnote” - Rocha, Rister Saulo Machado (2024)
This dissertation, developed within the Postgraduate Program in Arts at the Institute of Culture and Art of the Federal University of Ceará (PPGARTES/ICA/UFC), is part of an analysis to “Footnote” (2011), a movie directed by Israeli filmmaker Joseph Cedar. The methodological basis of the research was the bibliographical study of cinema and art authors, aiming to investigate the nuances of the work based on cinematographic development, bringing in its course disparate techniques and aesthetics using the same language. Thus, we try to use the concepts arising from the elements of cinematographic language to draw connections with the general purpose of carrying out a filmic analysis of the selected work.